Mycobacterium tuberculosis chorismate mutase: A potential target for TB. Issue 6 (15th March 2017) - Khanapur, Manjulatha; Alvala, Mallika; Prabhakar, Maddela; Shiva Kumar, K.; Edwin, R.K.; Sri Saranya, P.S.V.K.; Patel, Raj Kumar; Bulusu, Gopalakrishnan; Misra, P.; Pal, Manojit
Graphical abstract: Abstract: Mycobacterium tuberculosis chorismate mutase ( Mtb CM) catalyzes the rearrangement of chorismate to prephenate in the shikimate biosynthetic pathway to form the essential amino acids, phenylalanine and tyrosine. Two genes encoding chorismate mutase have been identified in Mtb . The secretory form, ∗ Mtb CM (encoded by Rv1885c) is assumed to play a key role in pathogenesis of tuberculosis. Also, the inhibition of Mtb CM may hinder the supply of nutrients to the organism. Indeed, the existence of chorismate mutase (CM) in bacteria, fungi and higher plants but not in human and low sequence homology among known CM makes it an interesting target for the discovery of anti-tubercular agents. The present article mainly focuses on the recent developments in the structure, function and inhibition of Mtb CM. The understanding of various aspects of Mtb CM as presented in the current article may facilitate the design and subsequent chemical synthesis of new inhibitors against ∗ Mtb CM, that could lead to the discovery and development of novel and potent anti-tubercular agents in future.